2000
DOI: 10.1377/hlthaff.19.4.51
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Use Among Undocumented Latino Immigrants

Abstract: Using data from a 1996/1997 survey of undocumented Latino immigrants in four sites, we examine reasons for coming to the United States, use of health care services, and participation in government programs. We find that undocumented Latinos come to this country primarily for jobs. Their ambulatory health care use is low compared with that of all Latinos and all persons nationally, and their rates of hospitalization are comparable except for hospitalization for childbirth. Almost half of married undocumented La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
201
1
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(217 citation statements)
references
References 5 publications
8
201
1
7
Order By: Relevance
“…These policies were put in place to discourage future immigrants from coming to the United States; however, several studies have suggested that this end will not be achieved-that is, the largest driver of immigration and where immigrants settle within the United States is in fact the availability of jobs, not health and social services. 38 Moreover, continuing to restrict immigrants' access to Medicaid for primary care, while allowing their access to Medicaid for emergency services, creates perverse incentives for providers and patients alike.…”
Section: Implications For Policymentioning
confidence: 99%
“…These policies were put in place to discourage future immigrants from coming to the United States; however, several studies have suggested that this end will not be achieved-that is, the largest driver of immigration and where immigrants settle within the United States is in fact the availability of jobs, not health and social services. 38 Moreover, continuing to restrict immigrants' access to Medicaid for primary care, while allowing their access to Medicaid for emergency services, creates perverse incentives for providers and patients alike.…”
Section: Implications For Policymentioning
confidence: 99%
“…Notable research demonstrated lower medical care use among undocumented Latinos; however, it did not estimate the comparative medical costs of all types of immigrants. 1 Similarly, other research has documented lower per capita health spending by the foreign-born but was unable to distinguish among the foreign-born by their naturalization or legal status. 2 The relative absence of reliable cost numbers partly reflects the strong emotion surrounding immigration throughout U.S. history.…”
mentioning
confidence: 99%
“…Immigrants from Latin America who have children in California are more likely to live in the south. 11 In addition, foreign-born immigrants with TB disease are less likely to seek medical care due to language, socioeconomic, and other barriers to accessing care, 22 and thus transmission of TB within the United States might be greater within these populations (including to children).…”
Section: Discussionmentioning
confidence: 99%